1995
DOI: 10.1046/j.1537-2995.1995.35195090662.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new citrate‐acetate‐NaCl platelet additive solution for the storage of white cell‐reduced platelet concentrates obtained from half‐strength CPD pooled buffy coats

Abstract: PAS 2 and Plasma-Lyte A make important contributions to platelet transfusion quality improvement and give an excellent CCl even after 4 days of storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 11 publications
3
51
1
Order By: Relevance
“…A small, nonrandomized clinical trial did not show a significant difference between PAS II PCs and plasma PCs, and one small prospective, randomized study reported that corrected count increments (CCIs) after transfusion with PAS II PCs were significantly lower. 11,12 Despite lower CCIs bleeding complications did not differ, and the latter study reported a significant reduction in transfusion reactions. 11 Observational analysis of the transfusion response of PAS II PCs and plasma PCs, used in the control arm of a randomized trial evaluating pathogeninactivated platelets (euroSPRITE), did not show significant differences.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…A small, nonrandomized clinical trial did not show a significant difference between PAS II PCs and plasma PCs, and one small prospective, randomized study reported that corrected count increments (CCIs) after transfusion with PAS II PCs were significantly lower. 11,12 Despite lower CCIs bleeding complications did not differ, and the latter study reported a significant reduction in transfusion reactions. 11 Observational analysis of the transfusion response of PAS II PCs and plasma PCs, used in the control arm of a randomized trial evaluating pathogeninactivated platelets (euroSPRITE), did not show significant differences.…”
Section: Introductionmentioning
confidence: 69%
“…11,12 Despite lower CCIs bleeding complications did not differ, and the latter study reported a significant reduction in transfusion reactions. 11 Observational analysis of the transfusion response of PAS II PCs and plasma PCs, used in the control arm of a randomized trial evaluating pathogeninactivated platelets (euroSPRITE), did not show significant differences. 13,14 A major drawback of these studies was the exclusion of patients with clinical factors known to increase platelet consumption.…”
Section: Introductionmentioning
confidence: 69%
“…No differences were observed, consistent with previously reported experience using T-Sol-plasma mixtures. 18 There was no statistically significant difference between test and reference populations with respect to duration of the first period of platelet support or total duration of platelet support ( Table 4). The average interval between platelet transfusions was computed for the first period of platelet transfusion, because all patients (n ϭ 103) underwent the first period of platelet support, and it was not significantly different for test and reference patients (Table 4).…”
Section: Platelet Count Increments 24 Hours Following Transfusion Andmentioning
confidence: 90%
“…18 PRP platelets are stored in 100% donor plasma as individual concentrates rather than as pools in a mixture of plasma with platelet additive solution. Therefore, PRP platelets prepared with photochemical treatment for pathogen inactivation may potentially demonstrate differences in clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmalyte was selected as it was FDA licensed for intravenous use, it had previously been used for platelet storage, and no FDA-licensed PAS solutions were currently available. [21][22][23][24][25][26] Unfortunately, many of our studies were completed before the FDA's post-torage viability criteria were formulated, and therefore a variety of control platelets were used. Because there was little, if any, difference between 1-day stored and fresh platelet viabilities (Table 1), if either of these platelets were used as controls, FDA poststorage viability criteria were evaluated for the test PAS platelets.…”
Section: Discussionmentioning
confidence: 99%